2003
DOI: 10.1177/104063870301500103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Serum Indirect Fluorescent Antibody Test with Two Western Blot Tests for the Diagnosis of Equine Protozoal Myeloencephalitis

Abstract: Abstract.A serum indirect fluorescent antibody test (IFAT) was compared with a Western blot (WB) and a modified Western blot (mWB) for diagnosis of equine protozoal myeloencephalitis (EPM). Using receiveroperating characteristic (ROC) analysis, the area under the curve of the IFAT was greater than the area under the curves of the WB and the mWB (P ϭ 0.025 and P ϭ 0.044, respectively). There was no statistically significant difference between the areas under the curves of the WBs (P Ͼ 0.05). On the basis of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 28 publications
1
72
0
1
Order By: Relevance
“…Immunoblot is considered the golden test for seroprevalence studies of S. neurona in horses, but it is expensive and laborious. DUARTE et al (2003) showed that IFAT could be an alternative to immunoblot for S. neurona antibody detection in horses, with good specificity and sensitivity. Cross-reactivity of both tests with other protozoa from donkeys is not known.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblot is considered the golden test for seroprevalence studies of S. neurona in horses, but it is expensive and laborious. DUARTE et al (2003) showed that IFAT could be an alternative to immunoblot for S. neurona antibody detection in horses, with good specificity and sensitivity. Cross-reactivity of both tests with other protozoa from donkeys is not known.…”
Section: Resultsmentioning
confidence: 99%
“…† Sarcocystis neurona agglutination test ). ‡ Indirect immunofluorescence antibody test (Duarte et al, 2003). killed, serum and CSF samples of all ponies were collected.…”
Section: Experimental Infection Of Horsesmentioning
confidence: 99%
“…Originally, a Western blot analysis was developed to detect antibodies to S. neurona in horses, which was reported to be able to differentiate between S. neurona and S. fayeri (Granstrom et al, 1993). Recently, another group of scientists reported that the Western blot analysis for S. neurona antibodies did not perform as well as an indirect immunofluorescence antibody test (IFAT) (Duarte et al, 2003).…”
mentioning
confidence: 99%
“…Descriptions of testing options and reported test performance are shown in Table 1 71, 72, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93. All tests can be performed on serum or CSF, and none is considered a gold standard.…”
Section: Immunodiagnostic Testingmentioning
confidence: 99%